2022
DOI: 10.3390/biology11040589
|View full text |Cite|
|
Sign up to set email alerts
|

RNA-seq and Mitochondrial DNA Analysis of Adrenal Gland Metastatic Tissue in a Patient with Renal Cell Carcinoma

Abstract: This study aimed to clarify whether genetic mutations participate in renal cell carcinoma (RCC) metastasis to the adrenal gland (AG). Our study analyzed whole mitochondrial gene and ribonucleic acid sequencing (RNA-seq) data from a male patient in his 60s with metastatic RCC. We confirmed common mutation sites in the mitochondrial gene and carried out Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis using RNA-seq data for RCC and adrenal carcinoma. Furthermore, we confirmed the common mutation sites of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Patients with RCC may develop metastatic disease at various anatomical sites. Synthesizing evidence from several researches conducted by Chatzizacharias NA et al, Komiyama T et al, Dudani S et al, and a study of IMDC, [49][50][51][52] we suggest that despite disparities in research outcomes regarding the common sites for RCC metastasis and discrepancies in the incidence of metastasis to different organs among distinct subtypes of RCC (Clear Cell RCC [ccRCC], papillary RCC, and chromophobe RCC), the predominant sites of metastasis can be delineated as follows: lungs, lymph nodes (LNs), bones, liver, brain, and adrenal glands. Notably, Gen'an Longren et al found that the therapeutic efficacy in mRCC may diverge contingent upon the specific organ site of metastasis.…”
Section: The Site Of Rcc Metastasismentioning
confidence: 99%
“…Patients with RCC may develop metastatic disease at various anatomical sites. Synthesizing evidence from several researches conducted by Chatzizacharias NA et al, Komiyama T et al, Dudani S et al, and a study of IMDC, [49][50][51][52] we suggest that despite disparities in research outcomes regarding the common sites for RCC metastasis and discrepancies in the incidence of metastasis to different organs among distinct subtypes of RCC (Clear Cell RCC [ccRCC], papillary RCC, and chromophobe RCC), the predominant sites of metastasis can be delineated as follows: lungs, lymph nodes (LNs), bones, liver, brain, and adrenal glands. Notably, Gen'an Longren et al found that the therapeutic efficacy in mRCC may diverge contingent upon the specific organ site of metastasis.…”
Section: The Site Of Rcc Metastasismentioning
confidence: 99%